TRANSLATION-ORIENTED TERMINOLOGY IN UKRAINE:EMERGENCE, FUNDAMENTALS AND PROSPETS - SAIKO, Mykhailo (Linguistic and Conceptual Worldviews, 2023)
The article focuses on the development of translation-oriented terminology as a separate convergent field of philological science in Ukraine, the actual date of which can rightly be considered 2020. It is stated that the impetus for its emergence was the limited reproductive (technique/transformational) approach of classical translation studies to the investigation of specialized translation. In addition to its object, subject and a number of tasks, the article identifies five conceptual positions of translation-oriented terminology, which significantly change the view on language and translation. Specifically, it posits that the main function of language and translation is creation rather than communication, whereas translation itself is a third-order simulacrum or hyperreality. Taking into account that the order cannot be born out of chaos, a creator, who relies on empirically verified language principles and laws, but not the observed facts, is an especially relevant figure in the field.The author distinguishes between translational, lexicographic, standard-related and situational areas of translation-oriented terminology research. The article provides a helpful list of resources for potential research in the German-Ukrainian direction, which could facilitate proper multidomain terminology regulation and standardization efforts. Based on the current needs of science and society, including the translation market, the outlined perspectives and tasks of translation-oriented terminology confirm its relevance and importance. It is noteworthy that translation- oriented terminology offers a significant advantage compared to other fields due to the applicability of its findings and standardization achievements, which initially address national priorities and ensure the provision of high-quality specialized translations.
Keywords: translation studies, terminology science, translation-oriented terminology, specialized translation, specialized lexicography, terminology standardization